Judicial Structure in India: Exploring the Organization and Functioning of the Indian Judiciary (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This chapter provides an introduction to the Indian court system and is written to be of interest to both those who learn about the Indian judicial system for the first time as well as experts looking for more nuanced overview. It describes the architecture of the Indian judiciary - in other words, the various types of courts and judges in the Indian judiciary and the hierarchy and relations between them. In particular, it focuses on how the Indian judiciary coordinates its behavior through both a system of stare decisis (ie judicial precedent) and internal administrative control. It describes the architecture of the Indian judiciary - in other words, the various types of courts and judges in the Indian judiciary and the hierarchy and relations between them.